Kebangkitan Penggunaan Candi Di Banyuwangi - Poniman Poniman (Jurnal Penelitian Agama Hindu, 2021)
The existence of Hindus in the archipelago was mostly centered on Java at first. This can be seen historical evidence in the form of a temple that is still remaining. However, actually the temple is a continuation of the sacred buildings in the previous civilization. There was a change in the treatment of the temple at that time because the worshipers had changed their understanding as a result of the new theological understanding he was introducing. Humans in carrying out religious traditions coupled with their level of intelligence, they will always reduce what exists and will create new civilizations to free them from the confinement of previous traditions. Likewise, the reappearance of the use of temples as part of Hindu religious life in Banyuwangi, which he had long abandoned as a means of rituals as a sign of revival. So it raises problems that need to be researched related to "What is the Basis for the Resurrection of the Use of Temples in Banyuwangi". The theory used in this research includes; Talcot Parsons' Structural Functional, Van Genneb's of Life Needs, Symbolic Interactionism, Theory of Religion. The methods used in qualitative research on the revival of the use of temples for the Hindi people in Banyuwangi include; In-depth Interviews, Participatory Observations, Documents, visual materials and data tracing published online.This study has the following results, including the basis for the revival of the use of temples: 1) There is a relationship between community systems, 2) the influence of reciprocal systems, 3) social integration, 4) social systems, 5) cultural revival, 6) agreement Together, 7) Historical Journeys.